The art of software testing - Myers, Glenford J. (John Wiley & Sons, 2004)
Provides a practical rather than theoretical discussion of the purpose and nature of software testing. Emphasizes methodologies for the design of effective test cases. Comprehensively covers psychological and economic principles, managerial aspects of testing, test tools, high-order testing, code inspections, and debugging. Extensive bibliography. Programmers at all levels, and programming students, will find this reference work indispensible.